Does digital cognitive behavioral therapy improve the insomnia and depression of workers to healthy levels? An open trial - Isa Okajima; Miho Suzuki; Noriko Tanizawa; Ikuo Kajiyama; Reiko Ichikawa; Jou Akitomi (BioPsychoSocial Medicine)
Abstract Background Cognitive behavioral therapy for insomnia (CBT-I) has a high potential for improving insomnia and depressive symptoms; however, it is unclear whether the improvement of symptoms reaches the level of healthy people without these symptoms. We aimed to examine whether digital CBT-I can improve the insomnia and depression symptoms of workers to healthy levels. Methods The study included 752 workers who were divided into four groups by the use of the cutoff scores of insomnia and depression scales: insomnia alone, depression alone, combined insomnia with depression (COMB), and healthy. All groups were administered digital CBT-I for 2 weeks, and changes were compared post-treatment and at 1- and 3-month follow-ups. Results A significant decrease in insomnia symptoms from post-treatment to the 3-month follow-up was found in the insomnia alone (Hedges’ g: 1.07–1.52) and COMB groups (g: 1.17–1.41). The COMB group also showed a significant decrease in depressive symptoms (g: 0.38–0.70). Moreover, there were significant differences in insomnia symptoms between both of the insomnia groups and the healthy group and in depressive symptoms between the COMB group and the healthy group, post-treatment and at the 1- and 3-month follow-ups. Conclusions Digital CBT-I effectively reduced insomnia and depressive symptoms but did not achieve the levels of healthy people within 3 months. Trial registration. UMIN, UMIN000050353. Registered 15 February 2023—Retrospectively registered, umin.ac.jp/ctr.